Pengetahuan dan Kepatuhan Minum Obat Pasien Hipertensi - Talango, Farid; Pohan, Vivi Yosafianti; Soesanto, Edy (FORIKES, 2024)
Hypertension patients' knowledge about the disease they suffer from can influence patient adherence with treatment, especially in terms of taking medication. The aim of this study was to determine the relationship between knowledge and medication adherence in hypertensive patients. This study was a systematic literature review using the “Preferred Reporting Items for Systematic Reviews and Meta-Analyzes” protocol. The databases used in this study were Google Scholar, ProQuest and PubMed, limited to publications from the last 5 years, namely 2019 to 2023. The keywords used were